Crescimento econômico e exportações por intensidade tecnológica das microrregiões nordestinas no período de 2010 a 2016: uma abordagem em dados em painel espacial - Souza, Adeilson Elias de (2020)
The objective of the research is to evaluate the spatial relationship between exports, disaggregated by level of technological intensity, and the economic growth of the Northeastern micro-regions in the period from 2010 to 2016. To this end, an exploratory analysis of spatial data (AEDE) was applied, on exports and economic growth, investigating the possibility of global spatial autocorrelation, with an index for the entire Northeast, and local, with the spatial relationship between the micro-regions of northeastern and its neighbors, individually, through the maps of clusters. In addition, the economic growth model proposed by Cuaresma and Wörz (2005) was estimated, using the spatial panel data econometric method with fixed effects. The results showed that exports from the Northeast are concentrated in products of low technological intensity, which have low productivity and added value. In spite of this, the estimated model of the research points out that these exports contribute to the reduction of the economic growth of the microregions of the Northeast, as they have lower productivity than the domestic sector, as argued by Cuaresma and Wörz (2005). In addition to exports, it was found that the northeastern microregions need investments in the infrastructure and R&D sectors, in order to develop economically. In this way, policies that attract and stimulate investments in these areas can be adopted, such as the improvement of ports and highways and the expansion of research and development expenses. In addition, low competition between local companies and relatively closed markets discourages companies from generating technology costs in their production processes, since they have less competition in the market. Thus, the economic growth of the microregions of the Northeast is also stimulated by the commercial opening, generating the need for local companies to produce goods with greater technological content.